Mesoscopic pinning forces in neutron star crusts. Issue 4 (2nd December 2015) - Seveso, S.; Pizzochero, P. M.; Grill, F.; Haskell, B.
Abstract: The crust of a neutron star is thought to be comprised of a lattice of nuclei immersed in a sea of free electrons and neutrons. As the neutrons are superfluid, their angular momentum is carried by an array of quantized vortices. These vortices can pin to the nuclear lattice and prevent the neutron superfluid from spinning down, allowing it to store angular momentum which can then be released catastrophically, giving rise to a pulsar glitch. A crucial ingredient for this model is the maximum pinning force that the lattice can exert on the vortices, as this allows us to estimate the angular momentum that can be exchanged during a glitch. In this paper, we perform, for the first time, a detailed and quantitative calculation of the pinning force per unit length acting on a vortex immersed in the crust and resulting from the mesoscopic vortex–lattice interaction. We consider realistic vortex tensions, allow for displacement of the nuclei and average over all possible orientations of the crystal with respect to the vortex. We find that, as expected, the mesoscopic pinning force becomes weaker for longer vortices and is generally much smaller than previous estimates, based on vortices aligned with the crystal. Nevertheless, the forces we obtain still have maximum values of the order of f pin ≈ 10 15 dyn cm −1, which would still allow for enough angular momentum to be stored in the crust to explain large Vela glitches, if part of the star is decoupled during the event.